CONCEPT OF HUMAN IN SHORT STORIES OF IVAN TURGENEV - Konul Aslanova (European Scientific Journal, ESJ, 2014)
Ivan Turgenev (1818- 1883) – a Russian novelist of the XIX centuries developed concept of human in his "Notes of a Hunter" which is the collection of short stories. As a representative of romanticism Turgenev comparing nature with society gives preference to the former. He expresses his sympathy to folk, peasants who are closer to nature, than representatives of higher strata. In his "Notes of a Hunter" Turgenev demonstrates a rich spectrum of the Russian national character. The "Notes of a Hunter" have also a generalized image that passes through all its parts. This is an image of nature which serves as a powerful force. Nature is considered by Turgenev as a measure of moral values as well as a criterion for assessing the actions of man, his inner world. Therefore, the characters of his works are often characterized by Turgenev through their relationship to nature, which affects to human and forms his inner world. Turgenev believes that human’s character is being formed under the influence of environment. However, when Turgenev says about environment he means not only society but also nature. Correlation between nature and society is manifested differently in characters of his literary heroes. Elements of nature are stronger in characters of peasants. But in characters of landowners elements of society take supremacy over the nature. Therefore, peasants are closer to the nature than landowners. Also they are spiritually and morally are higher than landowners. The description of literary characters allows Turgenev to develop a philosophical concept of human.